Covid-19 and business law : legal implications of a global pandemic - Trakic, Adnan (Berlin : De Gruyter, 2021)
This book will explore in a multi-jurisdictional approach potential legal impacts of a global pandemic like Covid-19 in the following areas: commercial transactions, employment relationships, hospitality and tourism, corporations and corporate governance, human rights and the rule of law, and protection of vulnerable groups like migrant workers.
Preface -- 1. COVID-19 and business law : challenges and opportunities / Adnan Trakic -- 2. The impact of COVID-19 on contractual obligations in Malaysia / Vazeer Alam Mydin Meera, Abdul Majid and Mei Yee Lee -- 3. COVID-19 and its influence on selected employment relationship issues / Ashgar Ali Ali Mohamed and Chithra Latha Ramalingam -- 4. Look what COVID-19 unveiled : the lack of insolvency protection by Malaysian travel companies / Joo-Ee Gan -- 5. Implications of the COVID-19 pandemic for the Malaysian Companies Act 2016 / Loganathan Krishnan -- 6. COVID-19 pandemic and competition law / Sunitha S. Sivakumaran -- 7. Discussions on human rights and the rule of law in the COVID-19 reality / Shanthy Thuraisingham and Danusha Rachagan -- 8. COVID-19 and trafficking of migrant workers for forced labour / Priya Sharma -- 9. The importance of legal services during the COVID-19 pandemic / Ridoan Karim -- 10. COVID-19 and business law : findings and recommendations / Adnan Trakic -- Notes on contributors.
Includes bibliographical references.
Keywords: Commercial law; COVID-19 (Disease) -- Law and legislation; COVID-19 Pandemic, 2020-; 0; Commercial law; COVID-19 (Disease) -- Law and legislation